2013
DOI: 10.3390/rs5073212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multi-Source and Multi-Temporal Remotely Sensed and Ancillary Data on the Accuracy of Random Forest Classification of Wetlands in Northern Minnesota

Abstract: Abstract:Wetland mapping at the landscape scale using remotely sensed data requires both affordable data and an efficient accurate classification method. Random forest classification offers several advantages over traditional land cover classification techniques, including a bootstrapping technique to generate robust estimations of outliers in the training data, as well as the capability of measuring classification confidence. Though the random forest classifier can generate complex decision trees with a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
154
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 79 publications
(86 reference statements)
7
154
1
Order By: Relevance
“…Optical and SAR imagery provide complementary information and are often used in combination, while addition of topographic variables has also been shown to improve wetland and other land cover classification [15,21,95,96]. This was confirmed in this study as variable importance analysis showed that shortwave-infrared reflectance (Landsat bands 5 and 7), PALSAR HV backscatter and several topographic variables (terrain classification index, relative slope position, elevation, and slope height, in order of importance) contributed most to overall classification accuracy.…”
Section: Random Forest Classifier Performance and Variable Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Optical and SAR imagery provide complementary information and are often used in combination, while addition of topographic variables has also been shown to improve wetland and other land cover classification [15,21,95,96]. This was confirmed in this study as variable importance analysis showed that shortwave-infrared reflectance (Landsat bands 5 and 7), PALSAR HV backscatter and several topographic variables (terrain classification index, relative slope position, elevation, and slope height, in order of importance) contributed most to overall classification accuracy.…”
Section: Random Forest Classifier Performance and Variable Importancementioning
confidence: 99%
“…The inclusion of SAR data had a relatively limited impact overall on the importance ranking of optical variables, although PALSAR HV outranked most variables when used in combination with optical variables. Corcoran, Knight and Gallant [95] discriminated upland, water, and wetland areas using RF with a similar assortment of predictors (e.g., Landsat 5 TM NIR and SWIR, elevation and curvature, hydric soils data, as well as PALSAR (L-band) cross-polarization (HV) data). Other studies have confirmed the importance of NDVI [14], NDMWI [97], Tasseled-cap components [98,99], and Landsat thermal band 6 as wetland predictors [95,98].…”
Section: Random Forest Classifier Performance and Variable Importancementioning
confidence: 99%
“…Values for the former provide an indication of the extent to which the variable generates homogeneous or pure nodes, while the latter is based on a relative change in accuracy as a result of the variable being randomly permuted or excluded from the model. In both cases, higher values indicate higher importance [14,38,44]. Importance values can also vary greatly among models built on the same predictor variables, although it has been shown that values become more stable when a high number of trees are built into the forest [38].…”
Section: The Random Forest Classifiermentioning
confidence: 99%
“…The random forest (RF) algorithm, an integrative classifier, has shown to be able to achieve high classification accuracy even when applied to analyze data with stronger noise [27,28]. Currently, the random forest classifier has been widely employed in the landcover classification of mesophyte environments, but is rarely used in the wetland classification for arid and semiarid areas [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%